How sustainable is Santiago de Chile? Current performance, future trends, potential measures. Synthesis report of the risk habitat megacity research initiative (2007-2011) - Kerstin Krellenberg; Jürgen Kopfmüller; Jonathan Barton (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
This report summarises the principal results of a threeyear joint German-Chilean research initiative. Its main objective is to provide answers for two questions. First, how sustainable is the Metropolitan Region of Santiago today? Second, what alternative future development options and potential measures are available to increase sustainability performance of the agglomeration until 2030? The report provides policy makers, practitioners, administrators, planners, and citizens concerned with different policy fields with the main project findings and recommendations. These results are based not only on profound scientific analyses, but also on intensive discussions with these stakeholders. By synthesizing the results, this report addresses the information needs of actors concerned with the overall metropolitan development and also those of the interested public.
Keywords: 330; Megastadt; Nachhaltige Entwicklung; Santiago (Chile)